Play in Early Childhood Education and the Perceived Impacts of Accountability and Rigor - White, Patricia; Martin, Barbara N; McDonald, Bryan (Advances in Social Sciences Research Journal, 2021)
Exploring explored principals' and teachers' perceptions concerning the role of play in early childhood programs was this quantitative inquiry. All early childhood participants identified play as a learning tool but noted it was being eliminated from the curriculum due to high stake accountability. There was a significant difference between administrators and early childhood educators concerning the purpose of play. Implications for early childhood curriculum and school district policy were determined.